2016
DOI: 10.1039/c5tb02251g
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic gelatin methacrylamide hydrogel scaffolds for bone tissue engineering

Abstract: The biomimetic GelMA scaffolds which have highly porous, interconnected macropores, and rough surface could promote ADSC to differentiate into osteoblasts and bone formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
53
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 52 publications
1
53
1
Order By: Relevance
“…In recent years, among hydrogels used in biomedical applications, gelatin methacrylate (GelMA) hydrogel became an attractive candidate due to gelatin's favorable biocompatible characteristics, and because it can be photocrosslinked to form a stable gel at body temperature (37°C) . Due to its compatibility, GelMA has been already proposed in some BTE studies for producing scaffolds for bone and chondral regeneration purposes . In vitro and in vivo mineralization characteristics of GelMA scaffolds and its composites have already shown very promising results for bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, among hydrogels used in biomedical applications, gelatin methacrylate (GelMA) hydrogel became an attractive candidate due to gelatin's favorable biocompatible characteristics, and because it can be photocrosslinked to form a stable gel at body temperature (37°C) . Due to its compatibility, GelMA has been already proposed in some BTE studies for producing scaffolds for bone and chondral regeneration purposes . In vitro and in vivo mineralization characteristics of GelMA scaffolds and its composites have already shown very promising results for bone regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its compatibility, GelMA has been already proposed in some BTE studies for producing scaffolds for bone and chondral regeneration purposes . In vitro and in vivo mineralization characteristics of GelMA scaffolds and its composites have already shown very promising results for bone regeneration. Furthermore, GelMA has exhibited superior properties of creating endothelial lined vasculature within engineered constructs .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyacrylamide, a macromolecule which can be synthesized by ultraviolet light and chemical initiator, is widely used in the biomedical field, such as for plastic surgery, drug release, and tissue engineering. [14][15][16] Inspired by the application of acrylamide in the bone tissue engineering technique, a durable hydrophilic polymeric film could be formed on the surface of metallic materials by UV irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that rhBMP-2 is efficient in skeletal defects repair in association with biomaterials by the recruitment and osteoinductive differentiation of MSC, angiogenesis and new bone integration. [8][9][10][11] To fully utilize the function of rhBMP-2 to induce bone formation, a series of biomaterial carriers have been explored to satisfy the applied requirements; for instance, biodegradable polymers, 12,13 polyelectrolyte multilayer coatings, 14,15 titanium, 16,17 hydrogels, 18,19 and inorganic nanoparticles. 20,21 Unfortunately, so far, even the most simple and traditional strategy for rhBMP-2 delivery, namely the usage of a collagen sponge carrier approved by the FDA, 22 oen results in protein denaturation and relatively unsatisfactory loading or releasing, which can lead to a supra-physiological dosage applied in the defect area, 7 and subsequently can result in offtarget severe side effects, such as the stimulation of bone resorption, edema, inammatory reactions, and undue tissue response in the host.…”
Section: Introductionmentioning
confidence: 99%